2020
DOI: 10.1080/17453674.2020.1774138
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic in Singapore: what does it mean for arthroplasty?

Abstract: Background and purpose — The ongoing Coronavirus Disease-19 (COVID-19) pandemic has taken a toll on healthcare systems around the world. This has led to guidelines advising against elective procedures, which includes elective arthroplasty. Despite arthroplasty being an elective procedure, some arthroplasties are arguably essential, as pain or functional impairment maybe devastating for patients, especially during this difficult period. We describe our experience as the Division of Arthroplasty in the hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Nine centers reported the number of elective orthopedic procedures performed both before and during the COVID-19 pandemic. 9 , 10 , 16 , 17 , 20 , 29 , 36 , 38 , 39 Cumulatively, the number of elective surgeries decreased by 80% (2013/17400, 0.20, CI: 0.12 to 0.29) ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…Nine centers reported the number of elective orthopedic procedures performed both before and during the COVID-19 pandemic. 9 , 10 , 16 , 17 , 20 , 29 , 36 , 38 , 39 Cumulatively, the number of elective surgeries decreased by 80% (2013/17400, 0.20, CI: 0.12 to 0.29) ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…2 The COVID-19 pandemic has produced a significant impact on arthroplasty procedures worldwide. [2][3][4][5] Previously, among the most common surgeries performed, the pandemic had lowered the number of arthroplasties performed worldwide. Studies worldwide have found significant decreases in arthroplasty procedures due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Studies worldwide have found significant decreases in arthroplasty procedures due to the pandemic. [4][5][6][7][8][9][10][11][12][13][14][15] As an orthopedic surgery requiring substantial contact between the surgeon and the patient, new protocols to reduce the infection have negatively impacted arthroplasty. 15 Postponement or cancellation of elective operations was rampant during the pandemic, alongside stricter procedures and guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The orthopaedic operations were subjected to one of the greatest relative declines in the normal medical activity in both the United Kingdom (UK) National Health Service and the United States (US) [ 1 , 2 ]. Although there are less abundant data for Asian regions, a major Singapore institution reported a 74% reduction in arthroplasties compared to the pre-pandemic levels [ 3 ], while a major orthopaedic department in Japan noted over 80 and 50% reductions in hip and knee arthroplasties respectively [ 4 ]. Similar patterns were observed in mainland China, Malaysia, and South Korea [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%